Proyeksi Produksi dan Keunggulan Komparatif Perdagangan Ubi Kayu Indonesia - Muhammad Ibnu (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Indonesia is one of the largest cassava importers among the ten cassava-producing countries. While there is a production surplus, Indonesia's cassava imports tend to increase yearly to meet industrial needs. This research has four objectives. First, to analyze (change) the production and trade of the world's largest cassava-producing countries in the future and the implications for Indonesia. Second, to evaluate the enabling environment for cassava production and marketing. Third, to identify the comparative advantages of Indonesia's cassava trade compared to other producing countries. Fourth, evaluate the potential for partnerships to increase Indonesian cassava production and marketing sustainability. This study used FAOSTAT data (1961-2020) projected to 15 years (2021-2035) with a double exponential smoothing method. Comparative advantages are evaluated with the Relative Export Advantage, Relative Import Advantage, Relative Trade Advantage, Net Export, and Grubel-Lloyd indexes. This study found that Indonesia's cassava harvested area will likely decrease while cassava imports will likely increase. Indonesia has a comparative advantage in exporting cassava. However, it is under-optimized due to inefficient cassava trades at the regional level and less successful cassava partnerships (between farmers and industry). This study recommends improving cassava production and trade conditions through improving enabling environments and collaborations between actors in the cassava chain.